Modeling of treadmill roller-skiing time-trial performance - Andersson, E. P.; Sundström, D. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: External power output in an endurance sport such as cross-country skiing can, from a physiological perspective, be explained as the sum of aerobic and anaerobic metabolic rates multiplied by the gross efficiency (GE). As cross-country skiing performance is highly dependent on all three performance factors, a model that could predict performance changes due to alterations in the respective factors would be beneficial for evaluating the training response and/or ability of an athlete. Therefore, this study was designed to develop and calibrate a performance model for time-trial (TT) roller-skiing on an indoor treadmill using the skating gear 3 subtechnique.